Pengaruh Media Gambar Berseri Terhadap Kemampuan Bercerita Pada Anak Di Taman Kanak-Kanak Sudha Kumara Denpasar - Sutrisna, I Putu Gede; Rismawan, Made; Nita Sari, Ni Kadek Ayu (Cetta: Jurnal Ilmu Pendidikan, 2024)
The basic ability to tell stories must be possessed by early childhood to improve speaking skills. However, in reality children's skill in story telling is still poor. Serial picture media is an alternative to improve storytelling skill in early childhood. To determine the effect of serial picture media toward storytelling skill in children at Sudha Kumara Kindergarten Denpasar. This study employed a pre-experimental one group pre-test and post-test design. The population of this study were all students of Kindergarten B with total sample 25 students recruited through total sampling technique. The data was collected using the skill of storytelling observation sheets and analyzed by using the non-parametric Wilcoxon Sign Rank Test. The statistical test showed that there was an effect of serial picture media on the skill of storytelling in children at Sudha Kumara Kindergarten Denpasar (p-value < 0.001, z = -4.492). There is an increase in children's storytelling skill after using serial picture media; so that, the teacher can provide serial picture as learning media in early childhood to improve storytelling skill.